Punctuated lives: the (un)making of Thwalwa’ed Subjects in Engcobo, South Africa - Ndlovu, Thatshisiwe (My University, 2022)
This study is about a particular group of women who were married through a specific cultural practice commonly known as ukuthwala (bride abduction) in South Africa, and it details the lives and experiences of these women. The study examines the technologies and mechanisms that sustain this cultural practice, and raises questions on who sanctions this cultural practice, how it is sustained and why. While arguing that ukuthwala is a violent cultural practice, it also uncovers women’s responses to this practice in their everyday lives. The thesis departs from the mainstream arguments on ukuthwala that focus on describing and detailing its scandalous nature by bringing into sharp focus discussions of the women’s own experiences and representations of this practice as one of the entry points in revealing the complex multiplicity of dynamics at play that are often missed in mainstream studies. While acknowledging that women have been silenced through and by this practice, the thesis brings women’s voices to the centre of its discussions and to knowledge production about the practice. It does so by prioritising the experiences of ukuthwalwa (those being abducted). Drawing on ethnographic research, including the life histories of thwalwa’ed women based on their own narration of their experiences, I ask how ukuthwala is perceived and experienced by these women and what the impact of dominant ideas is on women’s experiences of ukuthwalwa. I explore two related phenomena. Firstly, the complexities that pervade thwalwa’ed women’s lived lives, how these women live through ukuthwalwa, including ways that they find to resist, negotiate or adapt to their subjectivation. Secondly, the entities and technologies that ensure the continued existence of this practice, in particular, the ways in which culture works to enforce patriarchy through sanctioned forms of violence. The findings indicate that a thwala’ed subject is created through complex operations of violent power relations and within a framework of pain and suffering. I argue that understanding this complexity requires attention to how culture works in the interests of patriarchy as an ideological tool to impose a script on the lives of women such that they must come to terms with a new self – a thwalwa’ed self that struggles with itself. In that vein, I employ the notion of embodiment as the condition of “being in the world” (Csordas,1994) to uncover how the violence of ukuthwala, and the consequent pain and suffering are lived and embodied. Additionally, through the examination of the everyday tactics that these women utilise to navigate their lives, I argue that thwalwa’ed women are neither victims nor are they victors. I try to understand the women’s relationship to their constrained agency through the conceptual lens of ‘shifting vulnerabilities’ where women find ways of using their vulnerabilities to exercise their power in small acts in their everyday lives that sometimes exhibit resistance. Mostly, though, these acts exist within the accepted norms and expectations of the system that is designed to keep them in positions of subordination. In this way, I offer a reading of ukuthwalwa as one of a process of subjectivation (after Foucault) in which those on whom violence is enacted, act in their own interests, without accepting that which is imposed on them, even if only in small and hidden ways, reclaiming their own power to shape their subjectivities, albeit often without contesting or changing the system that oppresses them in its entirety.
A thesis submitted to the Faculty of Humanities in fulfilment of the requirement for the degree of Doctor of Philosophy, University of the Witwatersrand, Johannesburg
Keywords: Subjectivities; Patriarchy; Patriarchal violence; Thwalwa’ed woman; Ukuthwala